2020
DOI: 10.1182/blood.2019003358
|View full text |Cite
|
Sign up to set email alerts
|

Calreticulin haploinsufficiency augments stem cell activity and is required for onset of myeloproliferative neoplasms

Abstract: Mutations in JAK2, MPL, or CALR are detected in more than 80% of myeloproliferative neoplasm (MPN) patients and are thought to play a driver role in MPN pathogenesis via autosomal activation of the JAK-STAT signaling cascade. Mutant CALR binds to MPL, activates downstream MPL signaling cascades, and induces essential thrombocythemia in mice. However, embryonic lethality of Calr-deficient mice precludes determination of a role for CALR in hematopoiesis. To clarify the role of CALR in normal hematopoiesis and MP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
(67 reference statements)
0
12
0
Order By: Relevance
“…Alternatively, it is also possible that the amplification of HSCs observed in KI mice may correspond to an increase of a sub-population of active HSCs with more proliferating capacities, that would result in milder secondary engraftment. Interestingly, the group of K Shimoda showed that CALR wt is able to inhibit the CALR del52-induced competitive advantage, thus it is possible that the total absence of CALR wt in homozygous del52 or ins5 HSCs might explain their advantage on their heterozygous counterparts 27 . With age, preferentially homozygous del52 KI mice developed splenomegaly accompanied with a decrease in BM cellularity, while blood parameters remained constant.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it is also possible that the amplification of HSCs observed in KI mice may correspond to an increase of a sub-population of active HSCs with more proliferating capacities, that would result in milder secondary engraftment. Interestingly, the group of K Shimoda showed that CALR wt is able to inhibit the CALR del52-induced competitive advantage, thus it is possible that the total absence of CALR wt in homozygous del52 or ins5 HSCs might explain their advantage on their heterozygous counterparts 27 . With age, preferentially homozygous del52 KI mice developed splenomegaly accompanied with a decrease in BM cellularity, while blood parameters remained constant.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 Moreover, CALR haploinsufficiency in a CALR-mutated mouse model augmented hematopoietic stem cell activity in a JAK-STAT-signaling-independent manner, which was paramount for MPN onset. 41 Since the UPR pathways rely on protein degradation pathways, it will be of interest to elucidate whether the targeting of protein degradation pathways may be strategically combined with existing treatment modalities for CALR-mutated MPNs.…”
Section: Discussionmentioning
confidence: 99%
“…Among the MPL mutations, the most common are MPL W515L and MPL W515K [65]. Abnormal proliferation of hematopoietic stem cells results from spontaneous activation of the JAK-STAT pathway by MPL mutations [66,67]. Determining this gene is important because it can differentiate patients with a negative JAK2V617F mutation and those with a positive BCR-ABL mutation.…”
Section: Pathological Hematopoiesismentioning
confidence: 99%